Effects of strain rates on dynamic deformation behavior of Cu-20Ag alloy. (20th July 2021) - Song, Kexing; Geng, Yongfeng; Ban, Yijie; Zhang, Yi; Li, Zhou; Mi, Xujun; Cao, Jun; Zhou, Yanjun; Zhang, Xuebin
Graphical abstract: Highlights: Increase of strain rate reduced the adiabatic shear sensitivity of the Cu-20Ag alloy. The Cu-Ag interface has obvious orientation relationship with 111 C u / / ( 111 ) A g ; 1 ¯ 11 C u / / ( 1 ¯ 11 ) A g ; 2 ¯ 00 C u / / ( 2 ¯ 00 ) A g and [ 0 1 ¯ 1 ] C u / / [ 0 1 ¯ 1 ] A g with the increasing of strain rate. The increase of strain rate promotes the precipitation of Ag and increases the strain of interfaces in the microstructure. Abstract: Copper alloy is widely used in high-speed railway, aerospace and other fields due to its excellent electrical conductivity and mechanical properties. High speed deformation and dynamic loading under impact load is a complex service condition, which widely exists in the field of national defense, military and industrial application. Therefore, the dynamic deformation behavior of the Cu-20Ag alloy was investigated by Split Hopkinson Pressure Bar (SHPB) with the strain rates of 1000–25000 s −1, high-speed hydraulic servo material testing machine with the strain rates of 1–500 s −1 . The effect of strain rate on flow stress and adiabatic shear sensitivity was analyzed. The results show that the increase of strain rate will increase the flow stress and critical strain, that is to say, the increase of strain rate will reduce the adiabatic shear sensitivity of the Cu-20Ag alloy. The Cu-Ag interface has obvious orientation relationship with 111 C u / / ( 111 ) A g ; 1 ¯ 11 C u / / ( 1 ¯ 11 ) A g ; 2 ¯ 00 C u / / ( 2 ¯ 00 ) A g and [ 0 1 ¯ 1 ] C u / / [ 0 1 ¯ 1 ] A g with the increase of strain rate. The increase of strain rate promotes the precipitation of Ag and increases the number of interfaces in the microstructure, which hinders the movement of dislocations and improves the stress and yield strength of the Cu-20Ag alloy. The concentration and distribution density of dislocations and the precipitation of Ag were the main reasons improve the flow stress and yield strength of the Cu-20Ag alloy.